1979
DOI: 10.1111/j.1600-065x.1979.tb00266.x
|View full text |Cite
|
Sign up to set email alerts
|

Do Natural Killer Cells Engage in Regulated Reactions Against Self to Ensure Homeostasis?

Abstract: Host reactivities not requiring immunization in the mouse, especially natural resistance of irradiated animals to accept grafts of normal or malignant hemopoietic cells, were compared with NK activity against the YAC-1 lymphoma. The effects of several independent variables known to influence natural resistance in vivo had a similar effect on the NK system. Figure 12 lists an impressive array of shared properties and positive correlations. In contrast, the distinctions were few and minor. Many of the positive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
81
1

Year Published

1980
1980
1989
1989

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 267 publications
(88 citation statements)
references
References 76 publications
6
81
1
Order By: Relevance
“…This evidence strongly suggests that PMN are the cells mainly responsible for the protection in the early phase against influenza virus infection. It has been reported that NK cells are also sensitive to carrageenan but resistant to X-irradiation (Kiessling et al, 1977;Cudkowicz & Hochman, 1979) and that NK cells participate in non-specific resistance in several virus infections (Bukowski et al, 1983;Habu et al, 1984). In our studies, however, intraperitoneal administration of carrageenan before intranasal infection with the high dose of influenza virus did not increase virus titre in the lung at the early phase of infection (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This evidence strongly suggests that PMN are the cells mainly responsible for the protection in the early phase against influenza virus infection. It has been reported that NK cells are also sensitive to carrageenan but resistant to X-irradiation (Kiessling et al, 1977;Cudkowicz & Hochman, 1979) and that NK cells participate in non-specific resistance in several virus infections (Bukowski et al, 1983;Habu et al, 1984). In our studies, however, intraperitoneal administration of carrageenan before intranasal infection with the high dose of influenza virus did not increase virus titre in the lung at the early phase of infection (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Suppression was also reduced in glucose-free medium, which did not support the generation of RO. by natural killer cells can be stimulated by interferon (11) or interleukin-2 (12), and in the mouse, can be suppressed by a variety of agents including strontium-89 (13), carrageenans (14), silica particles (14), Co-rynebacterium parvum (15), estrogens (16), hydrocortisone (17), and prostaglandins (18). Certain of these agents appear to induce cellular suppression of natural killing (NK)', but the suppressor cells have been difficult to characterize, and the mechanism of suppression is unknown (15,17,19). The regulation of NK is of particular interest because of evidence that NK may be important in host defense against malignancy; the growth of certain tumors in vivo is inversely correlated with levels of NK, and spontaneous malignancy is increased when NK is deficient (20)(21)(22).…”
mentioning
confidence: 99%
“…The data, however, add to the thesis that NK cells may have a role in thymopoiesis. Cells with NK-like characteristics have been implicated in controlling cell growth and differentiation in haemopoiesis (25) and B cell differentiation (26). It might be expected that NK cells are involved in the control of haemopoiesis as all haemopoietic cells have similarities in their regulation (27).…”
Section: Discussionmentioning
confidence: 99%